Perlindungan Hukum Terhadap Pekerja Migran Indonesia: Analisis Kasus Tindak Pidana Perdagangan Orang di Kabupaten Wonosobo - Shafira Salwa Destriyanti; Susilo Wardani (IAIN Langsa, 2025)
This study aims to analyze the forms of legal protection provided to Indonesian Migrant Workers who are victims of human trafficking in Wonosobo Regency and to examine the implementation of migrant worker protection regulations at both the national and regional levels. This article is categorized as normative juridical research combined with an empirical juridical approach. The research method involves a literature review of laws and regulations, legal literature, and scientific journals, as well as interviews with the Indonesian Migrant Workers Union (SBMI) Wonosobo Branch as the primary data source. The results indicate that legal protection for migrant workers in Wonosobo Regency has not been implemented optimally, as reflected in the high number of non-procedural departures and ongoing cases of human trafficking due to weak migration literacy, inadequate supervision, and insufficient policy integration